Dissection of the DF27 paternal lineage. (December 2015) - Villaescusa, P.; Valverde, L.; Illescas, M.J.; de Pancorbo, M.M.
Abstract: The genetic evidence provided by the analysis of the Y chromosome is a valuable tool for the study of the evolution of paternal lineages. The dissection of S116, the major M269 subhaplogroup in Western and South-Western Europe uncovered an outstanding frequency of DF27 sublineage in the Basque region. In this study, a dissection of DF27 haplogroup was performed to the highest resolution to date in 340 individuals from the Basque Country. Our results describe frequency distribution patterns for some DF27 sublineages for the first time, and reveal a possible substructure of its paragroups.